Laboratory simulations of acid‐sulfate weathering under volcanic hydrothermal conditions: Implications for early Mars. Issue 3 (28th March 2014) - Marcucci, Emma C.; Hynek, Brian M.
Abstract We have completed laboratory experiments and thermochemical equilibrium models to investigate secondary mineral formation under conditions akin to volcanic, hydrothermal acid‐sulfate weathering systems. Our research used the basaltic mineralogy at Cerro Negro Volcano, Nicaragua, characterized by plagioclase, pyroxene, olivine, and volcanic glass. These individual minerals and whole‐rock field samples were reacted in the laboratory with 1 molal sulfuric acid at varying temperatures (65, 150, and 200°C), fluid:rock weight ratios (1:1, 4:1, and 10:1), and durations (1–60 days). Thermochemical equilibrium models were developed using Geochemist's Workbench. To understand the reaction products and fluids, we employed scanning electron microscopy/energy dispersive spectroscopy, X‐ray diffraction, and inductively coupled plasma‐atomic emission spectroscopy. The results of our experiments and models yielded major alteration minerals that include anhydrite, natroalunite, minor iron oxide, and amorphous Al‐Si gel. We found that variations in experimental parameters did not drastically change the suite of minerals produced; instead, abundance, size, and crystallographic shape changed. Our results also suggest that it is essential to separate phases formed during experiments from those formed during fluid evaporation to fully understand the reaction processes. Our laboratory reacted and model predicted products are consistent with the mineralogy observed at places on Mars. However, our results indicate that determination of the formation conditions requires microscopic imagery and regional context, as well as a thorough understanding of contributions from both experiment precipitation and fluid evaporation minerals.